1988
DOI: 10.1136/thx.43.6.456
|View full text |Cite
|
Sign up to set email alerts
|

Relation of perceived nasal and bronchial hyperresponsiveness to FEV1, basophil counts, and methacholine response.

Abstract: Perceived nasal and bronchial hyperresponsiveness to tobacco smoke and cold air were assessed in 912 working men in the Paris area. Baseline lung function measurements and peripheral leucocyte counts with standard differential counts were performed. At least one perceived nasal or bronchial hyperresponsiveness symptom was reported by 15-7%. Current smoking was significantly less frequent among those with cough induced by tobacco smoke. Rhinitis induced by cold air was associated with lower FEV, (p < 0 01) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…For example, the percentage of leukocytes in the blood is altered as a result of smoking, by the time of day and during menstruation (Kauffmann et al, 1988). We detected the baseline immune parameters in heatstressed pigs in earlier studies, such as the number of WBC and cell differential counts by using the Neubauer chamber method (Ju et al, 2011a).…”
Section: Discussionmentioning
confidence: 78%
“…For example, the percentage of leukocytes in the blood is altered as a result of smoking, by the time of day and during menstruation (Kauffmann et al, 1988). We detected the baseline immune parameters in heatstressed pigs in earlier studies, such as the number of WBC and cell differential counts by using the Neubauer chamber method (Ju et al, 2011a).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, an increased peripheral-blood eosinophil count is significantly associated with nonspecific airway hyperresponsiveness in asthmatic subjects [21]. Several studies have shown that high peripheral-blood eosinophil counts are associated with chronic respiratory symptoms (asthma, persistent wheeze, dyspnoea, chronic cough and phlegm) [19,[22][23][24][25][26]. The identification of eosinophilia as an independent risk factor for symptoms of cough and phlegm [23] and asthma [26] also suggests a role for eosinophils in the pathogenesis of COLD [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…As a part o f an ongoing study started in 1980/81 on the risk factors for chronic airflow limitations [9], 599 men working in the Parisian Police aged 28-58 years were selected in 1985/86 from the initial pop ulation to participate in a follow-up including also as a specific ob jective a prospective investigation o f UAD. The selected sample com prised: (i) 306 men with a previous history of asthma, wheezing, any perceived bronchial or nasal hyperresponsiveness (such as sneezes or runny nose or fit of coughing provoked by cold air and smoke), ec zema.…”
Section: Study Populationmentioning
confidence: 99%